The Correlation between Students’ Grammar Mastery and Their Writing Ability in Descriptive Text - Amelia, Rizky; Indrawati, Indrawati (EEdJ: English Education Journal, 2024)
This study aims to seek the correlation between students’ grammar mastery and their writing ability in descriptive text. This is correlational study was conducted to all seventh-grade students of a high school in Bangka Belitung, Indonesia as the population of the study as well as the sample since the number of the population below 50. This study used two kinds of test as the instruments to collect the data; a grammar mastery test which consists of 25 questions and a descriptive writing test. The Boardman scoring scale was used to measure the score of students’ writing. The result of this study showed the result of correlation coefficient computation was 0,305 and for the critical value from a significant level table 0.05/5% was 0,349. It is considered that the null hyphotesis (Ho) was accepted and the alternative hyphotesis (Ha) was rejected. In other words, there was no significance correlation between students’ grammar mastery and their writing ability. The writer found out that most of the students received good scores both in grammar and writing test but they had low scores in other aspects of writing such as; content, organization, word choice, and mechanics.